APLIKASI MOBILE COLLECTION BERBASIS ANDROID PADA PT. SUZUKI FINANCE INDONESIA - Sondang Sibuea; Mohammad Ikhsan Saputro; Agie Annan; Yohanes Bowo Widodo (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
Mobile collection application is a system to facilitate the process of monitoring and billing debtors at PT. Suzuki Finance Indonesia. Problems that often occur when billing is done by the ARO (Account Receiveble Officer) cannot be quickly monitored by the branch head. Also not known visit information quickly when billing. Therefore, in this research, an android-based mobile collection application will be built. So that monitoring and visit information can be obtained very quickly so that it can maximize the work of the branch head and ARO. The data collection method, the author uses field study techniques, interviews and uses library research methods with secondary data as the data source.